Strategic delivery of omega-3 fatty acids for modulating inflammatory neurodegenerative diseases - Chen, Yixin; Touboul, Roni; Chen, Yao; Chang, Chuchun L. (Frontiers in Aging Neuroscience, 2025)
ObjectivesEarly-life inflammatory events like infections and injuries may predispose the brain to Alzheimer’s disease (AD) by disrupting neurodevelopment and raising vulnerability. The association between early neuroinflammation and subsequent neurodegeneration leading to dementia remains unclear. We hypothesize that omega-3 (n-3) fatty acids (FA), especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), positively regulate neuro-immune cells, preserving their cell membrane structure and metabolic homeostasis. Our study examined whether strategic delivery of n-3 FA via injectable n-3 triglycerides (TG) can influence microglial lipid metabolism to prevent or delay AD progression.Methods and resultsWe characterized n-3 treatment effects on modulating lipid and metabolic homeostasis in microglia during the critical window of brain development. Our preliminary studies on determining the effects of early n-3 treatment on brain cell homeostasis indicate that perinatal bolus n-3 TG injections suppressed activation of gliosis-associated markers in young mice predisposed to AD (5xFAD) and yielded sustained regulatory effects on the expression of inflammatory molecules, such as interleukin-6 (Il6) and tumor necrosis factor-alpha (Tnfα), in adult brains. A significant increase in high-frequency ultrasonic vocalizations (USV) was observed in P6 5xFAD mice that received perinatal n-3 compared to vehicle control, implicating enhanced active communication patterns. Improvement in behavior deficits was observed in n-3-treated adult AD mice. Perinatal n-3 TG treatment modified brain lipid composition in young offspring, increasing key membrane lipid species, such as phospholipids (PL) and lysophospholipids (lysoPL). Pro-inflammatory sphingolipids associated with neurodegeneration, including lactosylceramide, were significantly lower in mice treated with n-3 than those in saline-treated AD mice.ConclusionOur study establishes a proof of principle for targeting brain immune cell metabolism with injectable n-3 TG to mitigate neuroinflammation in AD pathogenesis, paving the way for future research into early treatments for related central nervous system (CNS) disorders.